2004
DOI: 10.1111/j.1748-7692.2004.tb01150.x
|View full text |Cite
|
Sign up to set email alerts
|

RIVERINE HABITAT PREFERENCES OF BOTOS (INIA GEOFFRENSIS) AND TUCUXIS (SOTALIA FLUVIATILIS) IN THE CENTRAL AMAZON

Abstract: The distribution and density of the Amazon's two contrasting endemic dolphins–boto, or Amazon river dolphin, Inia geoffrensis, and tucuxi, Sotalia fluviatilis–were examined on two adjoining large rivers in western Brazil. Using a 17‐m river boat as a sightings platform, strip transects were used to cover areas within 150 m of the river margin and line transects were used in all other areas. Highest densities of both dolphins occurred near the margin, and lowest in the center of rivers. Seven different habitats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 5 publications
1
89
0
4
Order By: Relevance
“…(Ayres 1993), outras usam as várzeas em seus ciclos anuais e habitats complementares, como o peixe-boi da Amazônia, cujo ciclo de vida está diretamente associado às várzeas, onde se reproduzem e se alimentam durante os períodos de enchente e cheia, quando ocorre maior abundância de macrófitas aquáticas (da . Indiretamente essas alterações podem afetar as duas únicas espécies de cetáceos de água doce do Novo Mundo (Inia geoffrensis e Sotalia fluviatilis) que ocorrem em maior densidade nas áreas de várzea, em função da grande diversidade e abundância de peixes quando comparadas a outras áreas da sua distribuição (Martin et al 2004, Faustino & da Silva 2006.…”
Section: Eliminação Da Várzea Como Appunclassified
“…(Ayres 1993), outras usam as várzeas em seus ciclos anuais e habitats complementares, como o peixe-boi da Amazônia, cujo ciclo de vida está diretamente associado às várzeas, onde se reproduzem e se alimentam durante os períodos de enchente e cheia, quando ocorre maior abundância de macrófitas aquáticas (da . Indiretamente essas alterações podem afetar as duas únicas espécies de cetáceos de água doce do Novo Mundo (Inia geoffrensis e Sotalia fluviatilis) que ocorrem em maior densidade nas áreas de várzea, em função da grande diversidade e abundância de peixes quando comparadas a outras áreas da sua distribuição (Martin et al 2004, Faustino & da Silva 2006.…”
Section: Eliminação Da Várzea Como Appunclassified
“…), the Amazon River dolphin (Inia geoffrensis), the Irrawaddy dolphin (Orcaella brevirostris) and the tucuxi (Sotalia fluviatilis), also face comparable challenges of long-term survival (Reeves et al, 1991;Reeves and Chaudhry, 1998;Smith and Smith, 1998;Smith et al, 2001;Martin et al, 2004;Braulik, 2006), but demographic data for these species are still extremely limited. Although specific threats facing these freshwater cetaceans may vary geographically in their importance, common threats include substantial loss of effective habitat (Reeves et al, 1991;Braulik, 2006), increasing concentrations of persistent organic pollutants in cetacean tissue (Senthilkumar et al, 1999), and incidental fisheries by-catch (Martin et al, 2004). The drastic decline of the Yangtze finless porpoise in two decades as a result of rapid industrial and economic growth reveals how uncontrolled environmental deterioration threatens the future of freshwater cetaceans despite the potential for the massive scale of the Yangtze system to buffer anthropogenic impacts.…”
Section: Immediate Acts For Conservationmentioning
confidence: 99%
“…The former city (Porto Velho) presents a population of about 370 000 people, while in the latter, the number is > 60 000 (IBGE 2008). Although three out of the four dolphins analyzed by Torres et al (2007) have been found in a preserved environment (Mamirauá Reserve), data obtained from individually marked dolphins demonstrated that Tefé area is within the movement range of the boto population that inhabits the quoted reserve (Martin et al 2004), which could explain the occurrence of high concentrations of a pollutant of industrial and/ or urban origin (PCB) in an Amazonian reserve. Even though further investigations comprising a larger sampling are required before strong conclusions can be reached, it is important to highlight that ΣPCB concentrations in the subcutaneous adipose tissue of cetaceans from Amazon seem to mirror human presence in the concerned area.…”
Section: Cetaceans As Environmental Senti-nels For Micropollutant Conmentioning
confidence: 97%